2022
DOI: 10.1021/acs.inorgchem.2c01046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Water-Soluble Planar Cobalt(II), Nickel(II), and Copper(II) Hydroxo Clusters Using a (1,4,7-Triazacyclononane)cobalt(III) Complex as a Hydrolysis-Terminating Group

Abstract: We report on a group of planar cobalt(II), nickel(II), and copper(II) hydroxo clusters that have a definite composition and are water-soluble: [{Co(tacn)- 6), where tacn is 1,4,7triazacyclononane. The peripheral of each metal hydroxo cluster plane is chemically protected by the coordination of {Co III (tacn)(OH) 2 } + groups to prevent further hydrolysis. These clusters were synthesized by the reaction of an equimolar amount of [Co(tacn)(OH 2 ) 3 ] 3+ and cobalt, nickel, or copper salt at pH values in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For example, Isobe and co-workers reported that the {Cp*Rh} 2+ units (Cp* is C 5 Me 5 – ) of [{Cp*Rh} 4 V 6 O 19 ] dissociate in an acidic solution, and the addition of [Cp*Ir­(OH 2 ) 3 ] 2+ into the solution produces a series of [{Cp*Rh} 4– x {Cp*Ir} x V 6 O 19 ] clusters where x can take values of 1, 2, 3, or 4 . In other words, the organometallic cations of organo–POMs function as a protecting , or placeholder group by temporarily blocking the reactive sites of a POM anion, and they are exchangeable to other incoming metal cations (Scheme ). We were thus motivated to exploit this substitution reaction to functionalize organo–POMs with simple transition metal–aquo complexes that can provide association sites for various incoming ligands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Isobe and co-workers reported that the {Cp*Rh} 2+ units (Cp* is C 5 Me 5 – ) of [{Cp*Rh} 4 V 6 O 19 ] dissociate in an acidic solution, and the addition of [Cp*Ir­(OH 2 ) 3 ] 2+ into the solution produces a series of [{Cp*Rh} 4– x {Cp*Ir} x V 6 O 19 ] clusters where x can take values of 1, 2, 3, or 4 . In other words, the organometallic cations of organo–POMs function as a protecting , or placeholder group by temporarily blocking the reactive sites of a POM anion, and they are exchangeable to other incoming metal cations (Scheme ). We were thus motivated to exploit this substitution reaction to functionalize organo–POMs with simple transition metal–aquo complexes that can provide association sites for various incoming ligands.…”
Section: Introductionmentioning
confidence: 99%